The reception of ancient virtues and vices in modern popular culture : beauty, bravery, blood and glory - Almagor, Eran.; Maurice, Lisa, 1968- (Metaforms, 2017)
In Ancient Virtues and Vices in Modern Popular Culture , Eran Almagor and Lisa Maurice offer a comprehensive collection of chapters dealing with the reception of antiquity in popular media of the modern era (19th-21st centuries). These media include theatrical plays, cinematic representations, Television drama, popular newspapers or journals, poems and outdoor festivals. For the first time in Classical Reception Studies, ancient Jewish literature and imagery are included in the discussion. The focus of the volume is both the continuity and variance between ancient and modern sets of values, which appear in the new interpretations of the ancient stories, figures and protagonists.